Pemberdayaan ekonomi rakyat sebagai strategi pembangunan ekonomi unmat menghadapi lingkungan global - Syafaruddin Alwi (Universitas Islam Indonesia, 1997)
The empowerment of the mass economy has been of considerable interests among government, industrialists, and society lately. This issue is very significant to be emphasized here. Because participation of the mass is a significant element in the development process. There are several programs arranged, including the partnership program. The problem is how the shape of the partnership should be.Practically, the mass economy could not be empowered by the partnership program yet. Unfortunately, the partnership seems to be more politic rather than economic, whereas idealistically. the partnership should be able to create professionalism and both effective and responsive business network in the very dynamic environment. The partnership is focused on the three basic concept i.e. institutional, take and give, and also populist. As noted in the basic concept of the partnership, the strong and weak economic power have an equal take and give position. Therefore the partner ship should be beneficial to each other.